2019
DOI: 10.1111/1758-2229.12737
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Smithella‐dominating propionate oxidation in a sediment enrichment by magnetite and carbon nanotubes

Abstract: Summary Recent studies have shown that application of conductive materials including magnetite and carbon nanotubes (CNTs) can promote the methanogenic decomposition of short‐chain fatty acids and even more complex organic matter in anaerobic digesters and natural habitats. The linkage to microbial identity and the mechanisms, however, remain poorly understood. Here, we evaluate the effects of nanoscale magnetite (nanoFe3O4) and multiwalled CNTs on the syntrophic oxidation of propionate in an enrichment obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 84 publications
(111 reference statements)
0
28
0
1
Order By: Relevance
“…We also showed that hydrogenotrophic methanogenesis is more abundant and active than methylotrophic methanogenesis. Since mangrove sediments are rich in organic carbon, hydrogenotrophic methanogens could consume H 2 and cooperate with syntrophic microbes to degrade short-chain fatty acids [44,45]. Co-occurrence analysis also revealed a significant non-random association of methanogens and Woesearchaeota.…”
Section: Discussionmentioning
confidence: 96%
“…We also showed that hydrogenotrophic methanogenesis is more abundant and active than methylotrophic methanogenesis. Since mangrove sediments are rich in organic carbon, hydrogenotrophic methanogens could consume H 2 and cooperate with syntrophic microbes to degrade short-chain fatty acids [44,45]. Co-occurrence analysis also revealed a significant non-random association of methanogens and Woesearchaeota.…”
Section: Discussionmentioning
confidence: 96%
“…In a coculture of Geobacter and Methanosarcina strains, the presence of magnetite significantly promoted syntrophic CH 4 production from ethanol and acetate oxidation (Tang et al ., ). A number of environmental enrichment studies have shown that addition of magnetite stimulates CH 4 production from syntrophic oxidation of ethanol, propionate, butyrate, phenol and complex aliphatic hydrocarbon (Kato et al ., ; Viggi et al ., ; Li et al ., ; Zhang and Lu ; Jing et al ., ; Fu et al ., ; Leitao et al ., ; Yan et al ., 2018; Xia et al ., ). It has been hypothesized that the effective electric conductivity of magnetite facilitates the direct interspecies electron transfer (DIET) for the syntrophy (Kato et al ., ; Viggi et al ., ; Li et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Syntrophomonas are not known to oxidize propionate but butyrate and up to C 10 fatty acids [43]. The inclusion of Syntrophomonas in analysis was due to the fact that Smithella, which utilize the C 6 dismutation pathway, can release butyrate as an intermediate product into environment, which is then metabolized by Syntrophomonas [44]. A total of 30 OTUs belonging to ve syntroph genera were retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…Smithella in combination with Syntrophomonas are the next important group, while Syntrophobacter play only a minor role and that of Desulfotomaculum is negligible. Pelotomaculum and Smithella are known to use the methylmalonyl-CoA (MMC) pathway and the C 6 dismutation route, respectively [20,44,57,58]. Smithella are considered to tolerate a stricter thermodynamic condition than the MMC-utilizing syntrophs [59].…”
Section: Discussionmentioning
confidence: 99%